Effectiveness of a Motivational Smoking Reduction Strategy Across Socioeconomic Status and Stress Levels - Voigt, Elizabeth C.; Mutter, Elizabeth R.; Oettingen, Gabriele (Frontiers in Psychology, 2022)
Smoking consequences are seen disproportionately among low-SES smokers. We examine the self-regulatory strategy of mental contrasting with implementation intentions (MCII) as a smoking reduction tool and whether its effectiveness depends on subjective-SES. This pre-registered online experiment comprised a pre-screening, baseline survey, and follow-up. Participants reported past-week smoking, subjective-SES, perceived stress, and were randomized to an active control (n = 161) or MCII condition (n = 164). Data were collected via MTurk, during the U.S.’ initial wave of COVID-19. Participants were moderate-to-heavy smokers open to reducing or quitting. The primary outcome was self-reported smoking reduction, computed as the difference between recent smoking at baseline and follow-up. The secondary outcome was cessation, operationalized as self-reported seven-day point-prevalence abstinence at follow-up. Among those low—but not high—in subjective-SES, MCII (vs. control) improved smoking reduction by an average of 1.09 fewer cigarettes smoked per day, though this effect was not conclusive (p = 0.11). Similarly, quitting was descriptively more likely for those in the MCII than control condition, but the effect was nonsignificant (p = 0.11). Per an exploratory analysis, we observed that stress significantly moderated the condition effect (p = 0.01), such that MCII (vs. control) facilitated reduction among those experiencing high (p = 0.03), but not low stress (p = 0.15). Consistent with prior findings that MCII works best in vulnerable populations, MCII may be more effective for smoking reduction among high-stress than low-stress individuals. These findings contribute to growing research on income-related health disparities and smoking behavior change tools.